Determination of genotoxicity of classical swine fever vaccine in vitro by cytogenetic and comet tests - Genghini, R. (2006)
Chromosome damage in lymphocyte cultures induced by live virus vaccine against classical swine fever (CSF) has been observed in previous studies. In vivo cytogenetic tests were made with several doses of vaccines used in Argentina to control the disease. These studies have shown that genotoxic effects increased with dose. In the present study, two different in vitro assays were performed by recording the frequency of cells with chromosome alterations and by assessing the ability of the vaccine to damage DNA, using the single cell gel microelectrophoretic assay (comet test). Frequencies of cells with chromosomal alterations increased significantly when compared with controls and were dose (μl/ml) dependent: 0 = 1.23, 5 = 2.29, 10 = 5.42 and 20 = 11.71%. In the comet assay the variables measured, tail length (TL) and tail moment (TM), also increased. For control cultures TL was 2.32 μm, whereas with concentrations of 20 and 100 μl/ml TL were 12.47 and 42.3 μm, respectively. TM of control cultures was 0.18, whereas with vaccine concentrations of 20 and 100 μl/ml TM were 5.52 and 24.52, respectively. Comet frequency distributions differed significantly among treatments. These results agree with previous in vivo observations. Regarding CSF pathogeny, our results support a direct effect of CSF vaccinal virus on lymphocyte DNA. Genotoxicity of CSF vaccine was corroborated in vitro at the cytogenetic and molecular levels.